3-[2-(2-thienyl)ethoxy]phthalonitrile - Koysal, Yavuz; Isik, Samil; Iskeeli, Nazan Ocak; Durmuş, Mahmut; Ahsen, Vefa (Int Union Crystallography, 2006)
In the title compound, C14H10N2OS, the thienyl and phthalonitrile planes make a dihedral angle of 57.92 (2)degrees.